Integrasi Tunjuk Ajar Melayu dalam Pendidikan Karakter: Penguatan Pendidikan Karakter di Era Digital - Ramadhani, Rahma; Retnowati, Rini (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
Character education is a process of applying moral values that is carried out to shape and develop students' abilities to sort out good and bad actions, maintain good actions, and realize them in everyday life. In this digital era, it is undeniable that there is a negative impact of technology on the character of students such as cases of declining moral values, morals, and character of students. Local wisdom-based learning has a strategic position to strengthen character education. This study aims to describe the values in Tunjuk Ajar Melayu contained in the subject of Budaya Melayu Riau (BMR) elementary school as a strengthening of character education in the digital era. The method used in this research is library research. As a result, moral values in Tunjuk Ajar Melayu are very important to be understood and practiced, as an effort to strengthen character in the digital era. The values of character education that can be understood from the expressions contained in the Malay teaching instructions include the value of faith and piety to Allah SWT, the value of fairness and honesty, the value of independence and self-confidence, the value of unity and unity, the value of an unyielding spirit, the value of preserving and utilizing the surrounding nature, and the value of courtesy.